A4.16 Early bone loss in rat arthritis is predictive to disease severity. (13th February 2015) - Courbon, G; Rinaudo-Gaujous, M; Lamarque, R; Cleret, D; Vico, L; Marotte, H
Abstract : Background and objectives: Rheumatoid arthritis includes bone loss at different sites. Early subchondral bone loss is correlated with loss of joint function, whereas systemic bone loss is correlated with fracture risk. Recently, early bone microarchitecture alterations have been described in rat model of arthritis. We investigated in the rat adjuvant-induced arthritis (AIA) whether early bone loss in the prominent site (ankles) was a marker of other systemic bone damages and correlated with synovial inflammation outcome. Materials and methods: Rat AIA was induced (AIA rats) or not (control rats) at day0 in 6 weeks female Lewis rats. Clinical parameters including articular index (AI) were monitored during the experiment, before and after arthritis clinical onset. Bone microarchitecture, bone mineral density (BMD) profiles were obtained by µ-computed tomography (µ-CT) and dual energy x-rays absorptiometry (DXA) x-rays, respectively, at day0, the arthritis onset, and day17. Local sites analysed included the main four ankle bones: navicular, talus, cuboid, and calcaneus bones. Systemic sites enclosed tibia and 2 nd lumbar vertebra (LV2). Bone histology was performed only at day of sacrifice (day17). Results: In this experiment, arthritis onset was at day10, with different levels of arthritis. At day 10, early microarchitecture changes were detected in the four ankle bones analysed. Decreased trabecular bone volume and thickness (p < 0.01) and increased cortical porosity (p < 0.01) were observed by µ-CT in AIA compared to control rats. At day17, extended ankle bone changes were assessed by µ-CT and correlated together with histology assessment. Bone mineral density (BMD) was highly decreased in AIA rats ankle compared to control rats (-22%; p < 0.001). There was also a systemic BMD decreased in AIA rats compared to control rats (tibia -16%, LV2 -15%; p < 0.001 for both). In AIA rats, ankle-tibia-LV2 BMD values were correlated together (r from 0.77 to 0.87; p < 0.001 for all), while BMD values were randomly distributed in control rats. In AIA rats, early bone microarchitecture changes correlated with arthritis severity at day17, in both synovial inflammation and bone loss parameters (for instance, bone volume at day10 and AI at day17, r = -0.90, p < 0.001). Conclusions: Bone microarchitecture changes at arthritis onset in the rat AIA model are observed in four bones of ankle. These early changes are correlated with arthritis outcome at day17, in terms of synovial inflammation, local joint destruction, and systemic bone loss.